Modelo de programação linear inteira mista para o planejamento da cadeia de suprimentos do hidrogênio verde: um estudo de caso - Camelo, Mirella Martins (2024)
The green hydrogen supply chain has an increasing interest as a promising alternative for a low-carbon economy transition. Challenges related to the production, storage, and distribution infrastructure of this fuel are widely investigated in this field. Therefore, this Dissertation aims to propose a mixed-integer linear programming model for the optimized green hydrogen supply chain design, taking into account the production of renewable energy and hydrogen, the storage and distribution from the production plants to the final demand. The objective function is to minimize the total costs, considering the available technological options at each stage. With this model, the quantity, type, and location of production plants, transportation modes, and storage facilities will be determined to achieve an efficient and cost-effective operation in its application in the case study located in Ceará. Three scenarios epresenting cases of increased demand in the Ceará State were simulated to demonstrate a practical application of the proposed model. The costs per unit of produced hydrogen decreased by 1.1%, 46.5%, 77.7%, and 54.6% for feedstock, production, distribution, and storage, respectively. Consequently, the results of this study offer valuable insights for decision-making in terms of infrastructure and operation of the optimized supply chain.